2023
DOI: 10.1038/s41467-023-37348-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tagged glycans with a protein nanopore

Abstract: Structural complexity of glycans derived from the diversities in composition, linage, configuration, and branching considerably complicates structural analysis. Nanopore-based single-molecule sensing offers the potential to elucidate glycan structure and even sequence glycan. However, the small molecular size and low charge density of glycans have restricted direct nanopore detection of glycan. Here we show that glycan sensing can be achieved using a wild-type aerolysin nanopore by introducing a facile glycan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…Recently, we proposed a glycan derivatization strategy and thus achieved nanopore-based single-molecule sensing of a diverse set of glycans based on an Aerolysin (AeL) nanopore (Figure 8A). 4 Glycan derivatization was completed by a reductive amination reaction between the glycan reducing end and an aromatic amine (Figure 8B). In sharp contrast to the native sialyllactoses, which showed no detectable current blockage signal, we found that the aromatic compound (e.g., 1methoxy-4-phenoxybenzene (MPB))-tagged sialyllactoses (i.e., MPB-tagged 6SL and 3SL) elicited significant current blockage signals in the AeL nanopore under a bias voltage of +100 mV (Figure 8C).…”
Section: Glycan Analysis With Nanofluidic Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we proposed a glycan derivatization strategy and thus achieved nanopore-based single-molecule sensing of a diverse set of glycans based on an Aerolysin (AeL) nanopore (Figure 8A). 4 Glycan derivatization was completed by a reductive amination reaction between the glycan reducing end and an aromatic amine (Figure 8B). In sharp contrast to the native sialyllactoses, which showed no detectable current blockage signal, we found that the aromatic compound (e.g., 1methoxy-4-phenoxybenzene (MPB))-tagged sialyllactoses (i.e., MPB-tagged 6SL and 3SL) elicited significant current blockage signals in the AeL nanopore under a bias voltage of +100 mV (Figure 8C).…”
Section: Glycan Analysis With Nanofluidic Sensorsmentioning
confidence: 99%
“…This paper presents a dynamic capture approach for sialylated glycopeptides through a dynamic covalent chemistry strategy . Identification of Tagged Glycans with a Protein NanoporeLiM.XiongY.CaoY.ZhangC.LiY.NingH.LiuF.ZhouH.LiX.YeX.PangY.ZhangJ.LiangX.QingG. Li, M. Xiong, Y. Cao, Y. Zhang, C. Li, Y. Ning, H. Liu, F. Zhou, H. Li, X. Ye, X. Pang, Y. Zhang, J. Liang, X. Qing, G. 1737Nat. Commun.202314 …”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most cancer biomarkers identified to date are glycoproteins, of which the most well known are CA125, AFP, and CA50. In addition, sialylated glycans also mediate the entry of some human viruses, such as the influenza viruses and the Middle East respiratory syndrome coronavirus, into host cells; in particular, different linkage isomers of glycans can lead to distinctly different biological effects [ 10 – 12 ]. The aforementioned examples highlight the enormous significance of saccharides and glycans in biological systems, although their precise recognition, identification, and comprehensive analysis remain exceptionally challenging.…”
Section: Introductionmentioning
confidence: 99%